Multisensory Learning Activities in Enhancing Young Children’s Learning Readiness: A Qualitative Study in Indonesian Early Childhood Settings - Rarawati, Ida (CV. Chandralia Bintang Pustaka, 2026)
Multisensory learning has been increasingly recognized as an effective pedagogical approach to support young children’s holistic development, particularly in enhancing learning readiness. However, empirical qualitative evidence from Indonesian early childhood education contexts remains limited. This study aims to explore the implementation of multisensory learning activities and examine their impact on children’s attention, emotional regulation, and task persistence. A qualitative descriptive design was employed to capture the lived experiences of participants in a natural classroom setting. Data were collected through semi-structured interviews with one teacher and one parent, as well as classroom observations involving five children aged five to six years in an early childhood education center in Mustika Jaya, Indonesia. The data were analyzed using thematic analysis to identify recurring patterns and meanings. The findings revealed three main themes: (1) multisensory learning enhances children’s attention and sustained focus, (2) multisensory activities improve emotional regulation and self-confidence, and (3) multisensory learning strengthens learning readiness and task persistence. Children demonstrated increased engagement, reduced distraction, greater emotional stability, and improved ability to complete tasks independently. The study highlights the importance of integrating sensory-rich, interactive, and child-centered learning experiences in early childhood education. It also emphasizes the critical role of teachers and parents in facilitating and reinforcing multisensory learning. These findings contribute to the theoretical understanding of learning readiness as a multidimensional construct and provide practical implications for educators and policymakers to design inclusive and developmentally appropriate learning environments. Future research is recommended to explore the long-term impact of multisensory learning across diverse educational contexts.